International Adjustment in the New Neoclassical Synthesis - Marvin Goodfriend (Kiel Institute for the World Economy (IfW), 2007)
This paper applies principles of the New Neoclassical Synthesis (NNS) to questions of international trade and financial adjustment. The analytical framework is a 2-country, 2-good, 2-period model designed to explore the behavior of the balance of payments, the terms of trade, and aggregate fluctuations in terms of interest rate and exchange rate policies practiced by the world's most important central banks.1 In keeping with NNS principles, the analysis begins by specifying a flexible-price International Real Business Cycle (IRBC) model in which aggregate fluctuations are entirely real in nature and there is no role for monetary stabilization policy. The IRBC model serves as the core of an International New Neoclassical Synthesis (INNS) model which includes money prices and wages, a nominal exchange rate, nominal interest rates, and costly price adjustment. Frictions associated with the use of money have two important consequences. First, monetary frictions expose the INNS economy to inefficient aggregate fluctuations relative to the IRBC core. Second, monetary frictions provide the leverage for interest rate policy to influence real aggregate variables. The New Neoclassical Synthesis provides strategic and tactical direction for interest rate policy, recommending the adoption of a flexible exchange rate to enable each country to target domestic inflation independently to make the INNS economy behave like its IRBC core. In practice, monetary policy frictions associated with modeling, forecasting, and measurement inevitably produce inefficient outcomes relative to the IRBC core. The paper explores inefficiencies that occur because interest rate policy doesn't act flawlessly and those that occur because a country fixes its exchange rate, or because of credibility crises that manifest themselves as "inflation scares" in a flexible exchange rate regime or as "devaluation scares" in a fixed exchange rate regime.
Keywords: 330